2022
DOI: 10.3389/fmicb.2022.936272
|View full text |Cite
|
Sign up to set email alerts
|

Non-structure protein ORF1ab (NSP8) in SARS-CoV-2 contains potential γδT cell epitopes

Abstract: Upon activation by the pathogen through T-cell receptors (TCRs), γδT cells suppress the pathogenic replication and thus play important roles against viral infections. Targeting SARS-CoV-2 via γδT cells provides alternative therapeutic strategies. However, little is known about the recognition of SARS-CoV-2 antigens by γδT cells. We discovered a specific Vγ9/δ2 CDR3 by analyzing γδT cells derived from the patients infected by SARS-CoV-2. Using a cell model exogenously expressing γδ-TCR established, we further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(41 reference statements)
0
1
1
Order By: Relevance
“…39 Transfected Vd2 TCRs from COVID-19 patients activated in response to epitopes that were present on non-structural protein 8 (NSP8), a protein encoded in the SARS-CoV-2 genome. 40 However, we did not find any evidence of disease severity being associated with expansions of the similar TCRs in COVID-19. We showed that CD27 À Vd2 effector T cell proportions correlated with disease severity.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…39 Transfected Vd2 TCRs from COVID-19 patients activated in response to epitopes that were present on non-structural protein 8 (NSP8), a protein encoded in the SARS-CoV-2 genome. 40 However, we did not find any evidence of disease severity being associated with expansions of the similar TCRs in COVID-19. We showed that CD27 À Vd2 effector T cell proportions correlated with disease severity.…”
Section: Discussioncontrasting
confidence: 66%
“…In addition, another study confirmed these results and also showed that these cells had enhanced cytolytic potential, killed influenza‐infected cells (A and B) and utilized a public Vγ9 TCR CDR3 paired to various Vδ2 CDR3s 39 . Transfected Vδ2 TCRs from COVID‐19 patients activated in response to epitopes that were present on non‐structural protein 8 (NSP8), a protein encoded in the SARS‐CoV‐2 genome 40 . However, we did not find any evidence of disease severity being associated with expansions of the similar TCRs in COVID‐19.…”
Section: Discussionmentioning
confidence: 70%